Radiation shielding of upgraded accelerator LUE-10M - Mitrochenko, V.V.; Pugachev, G.D.; Uvarov, V.L.; Repikhov, O.A.; Tenishev, A.Eh.; Shestakova, V.S. (Вопросы атомной науки и техники, 2018)
The LUE-10M accelerator operating in NSC KIPT is used for sterilization of a considerable amount of medical products in Ukraine, thereby contributing to national security and health of population. However, by the present time the accelerator component parts have become worn out and outdated. So, it is anticipated that the LUE-10M should be upgraded on the basis of new hardware components with arrangement in the same premises of a new 10 MeV radiator with average beam current up to 2 mA. The calculations performed have demonstrated that the characteristics of the actual LUE-10M shield and ventilation systems meet the requirements of the guidelines provided that the accelerator is operated at the design parameters of the beam.